Liquid CO2-based coating for dense CuInxGa1-xS2 film fabrication - Nursanto, Eduardus Budi; Park, Se Jin; Hwang, Yun Jeong; Kim, Jaehoon; Min, Byoung Koun (ELSEVIER SCIENCE BV, 2017)
A liquid CO2 (l-CO2)-based coating technique is used for the pore-filling of a porous copper indium gallium sulfide (CuInxGa1-xS2, CIGS) film synthesized by a solution-based method. In the l-CO2-based coating, copper and indium precursors dissolved in l-CO2 are deposited on the porous copper indium gallium oxide film, followed by low-temperature sulfurization. After the high-temperature sulfurization of the deposited film with the l-CO2-based coating, a highly dense CIGS film with almost complete pore-filling is obtained. The use of an indium rich solution in l-CO2 leads to the formation of near stoichiometric ratio of Cu:(In + Ga) that improves the pore filling behavior. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: SUPERCRITICAL CARBON-DIOXIDE; MESOPOROUS TIO2 FILM; REACTIVE DEPOSITION; CONFORMAL COPPER; QUANTUM-DOTS; SOLAR-CELLS; NANOPARTICLES; GROWTH; CO2; PD